The first stage of numeral classification in the Chinese language - L.L. Bankova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The study of Chinese numerals prompts the need to classify them. The following major challenges are commonly faced during this step: confusion of classifying bases; considering Chinese numerals through the prism of numeral classifications for other types of languages; having no clear definition of a numeral. In view of the above, this paper provides the author's vision of numerals as a class of words performing the quantitative function and denoting abstract numbers, a number of objects, or mental categories related to number, order of count, multiplicity, and summation. The paper focuses on the first stage of classifying the Chinese numeral, thereby laying a foundation for further research. Researchers fail to agree which numerals – quantitative, ordinal, multiple, approximate, or interrogative – should be considered as the basic ones and which ones should be marked as belonging to the secondary level of classification. As a result of the critical analysis of all the possible variations, starting with two-positional classifications and ending with multi-positional ones, the conclusion was made that at the first stage of analysis of Chinese numerals it is reasonable to divide them into quantitative and ordinal.